Self-Compassion Overview in High School Students - Syahril, M. Fiqri; Krismona, Elwas Berdha; Yanti, Nengsi Dahma; Andrianie, Santy; Wulandari, Arifah (International Journal of Applied Guidance and Counseling, 2025)
Self-compassion is defined as a form of accepting oneself in one's condition, and it also includes incidents of failure, difficulties, or bad things experienced by individuals. To participants, self-compassion is a duty for high school-age individuals to develop in aspects of personal development, including measuring one's size in an organisation and providing guidance and counselling in schools. The purpose of the study. This is a known description of self-compassion participants studied at State Senior High School 2, Subang. The methods used are quantitative with a descriptive statistical approach. Data was collected using the Self-Compassion scale for 401 participants in the education class X at Senior High School 2 Subang. The study results conclude that as many as 55 participants educated their self-compassion in category low, 274 participants educated their self-compassion in category moderate, and 72 participants educated their self-compassion in category high.